Community-Based Ecotourism Development and Sustainable Rural Entrepreneurship in Indonesia - Fidya Pramesti; Randika Shafly Fawwaz; Mahfud Heru Fatoni; Aswanto Aswanto; Eko Sutrisno (Journal of Management, Entrepreneurship, and Tourism, 2026)
Community-based ecotourism has increasingly been promoted as a strategic pathway for fostering sustainable rural development, yet empirical evidence explaining how it systematically enables sustainable rural entrepreneurship remains limited, particularly in developing country contexts. This study examines the relationship between community-based ecotourism development and sustainable rural entrepreneurship in Indonesia, emphasizing the roles of participation, local governance, and environmental management. Employing an empirical quantitative design, data were collected from rural tourism communities managing ecotourism destinations through structured questionnaires administered to community entrepreneurs, cooperative leaders, and local managers. The data were analyzed using Partial Least Squares Structural Equation Modeling to assess measurement validity and test structural relationships among latent constructs. The findings demonstrate that community-based ecotourism development has a significant positive effect on sustainable rural entrepreneurship, reflected in enhanced economic viability, social value creation, and environmental orientation of rural enterprises. The results further reveal that collective learning, social capital, and institutional embeddedness mediate this relationship, transforming tourism activities into resilient and adaptive entrepreneurial systems. The study contributes to the literature by empirically positioning community-based ecotourism as a developmental platform that integrates governance, entrepreneurship, and sustainability, offering practical insights for rural development policy and community empowerment strategies.